Multivariate Chiral Covalent Organic Frameworks with Controlled Crystallinity and Stability for Asymmetric Catalysis. - Zhang, Jie; Han, Xing; Wu, Xiaowei; Liu, Yan; Cui, Yong (Journal of the American Chemical Society, 2017)
The modular construction of covalent organic frameworks (COFs) provides a convenient platform for designing high-performance functional materials, but the synthetic control over their chirality has been relatively barely studied. Here we report a multivariate strategy to prepare chiral COFs (CCOFs) with controlled crystallinity and stability for asymmetric catalysis. By crystallizing mixtures of triamines with and without chiral organocatalysts and with a dialdehyde, a family of two- and three-component 2D porous CCOFs that adopt two different stacking modes is prepared. The organocatalysts are periodically appended on the channel walls, and their contents, which can be synthetically tuned using a three-component condensation system, greatly affect the chemical stability and crystallinity of CCOFs. Specially, the ternary CCOFs displayed relatively high crystallinity and stability compared with the binary CCOFs. Under harsh conditions, the ternary CCOFs can serve as efficient heterogeneous catalysts for an asymmetric aminooxylation reaction, an aldol reaction, and the Diels--Alder reaction, with the stereoselectivity and diastereoselectivity rivaling or surpassing the homogeneous analogues. This work not only opens up a new synthetic route toward CCOFs, but also provides tunable control of COF crystallintity and stability and, in turn, the properties.